Reliability, familiarization effect, and comparisons between a predetermined and a self-determined isometric-squat testing protocol - McGoldrick, C. D.; Iacono, A. D.; Morgan, O. J.; Nayler, J.; Buchanan, J.; McCart, C.; Unnithan, V. B. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study examined the interday reliability of a predetermined and a self-determined isometric-squat test among youth soccer players. Familiarization effects were evaluated to determine the minimum number of trials necessary to obtain consistent outputs. Finally, differences between protocols were evaluated.